Corrigendum for: Evaluation of Blood-Brain Barrier Integrity by the Analysis of Dynamic Contrast-Enhanced MRI - a Comparison of Quantitative and Semi-Quantitative Methods - Kala, David; Šulc, Vlastimil; Olšerová, Anna; Svoboda, Jan; Prysiazhniuk, Yeva; Pošusta, Antonín; Kynčl, Martin; Šanda, Jan; Tomek, Aleš; Otáhal, Jakub (Physiological research, 2023)
List of changes: On the basis of author's request the publisher of Physiological Research decided to change the license of the article to CC BY license.